Private enforcement of European competition and state aid law current challenges and the way forward - Wollenschläger, Ferdinand; Wurmnest, Wolfgang, 1969-; Möllers, Thomas M. J. (International competition law series ;, 2020)
'Private Enforcement of European Competition and State Aid Law' addresses two key areas of European Union (EU) law, EU competition law and EU State aid law, in which private law enforcement has become increasingly important over the past years. The overlapping EU regimes of competition law and State aid law provide mechanisms allowing private plaintiffs to claim compensation for losses or damages. It is thus of significant practical value to provide, as this book does, analysis and guidance on achieving enforcement of such claims, written by renowned authorities in the two fields. This will be a unique new work, combining practical analysis with informed debate on understanding the rules of private enforcement on the EU level and the covered Member States.